Обоснование целесообразности совместного использования обмоток включения и отключения в бистабильных электромагнитных приводах вакуумных выключателей - Бугайчук, В.М.; Клименко, Б.В.; Емельянов, В.Л. (Електротехніка і електромеханіка, 2011)
The possibility and feasibility of joint use of the windings on and off when the relevant transactions vacuum circuit breaker with bistable electromagnetic actuators. An analysis of the design characteristics of the bistable solenoid for vacuum circuit breaker you with separate windings, and sharing on and off.